Relationship between family support and breastfeeding self-efficacy towards providing breast milk to breastfeeding mothers - Abel Kurnia Desladima; Sri Mulyani; Yuliana Yuliana; Luri Mekeama; Meinarisa Meinarisa (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Breast milk feeding has a significant positive impact on maternal and infant health, providing protection against various acute and chronic diseases. To improve providing breast milk success, breastfeeding self-efficacy as an internal factor, and external factors obtained from family support. Purpose: to decide the impact of family support and breastfeeding self-efficacy on providing breast milk between breastfeeding mothers. Method: This research used a quantitative retrospective study approach. The population consisted of 190 breastfeeding mothers, with a minimum sample size of 71 respondents choice using accidental sampling. Data collection used questionnaires on providing breast milk, family support, and the Breastfeeding Self-Efficacy Scale Short Form (BSES-SF). The data was analyzed use the chi-square test to see the relationship between the variables. Results: 90% of respondents received good family support, and 87% have high breastfeeding self-efficacy. 87% of respondents exclusively breastfed, while 13% did not. The chi-square test output indicates a significant relationship between family support and breast milk feeding (p-value <0.001), and a significant relationship between breastfeeding self-efficacy and breast milk feeding (p-value <0.001). Conclusion: There is a significant relationship between family support and breastfeeding self-efficacy towards providing breast milk to breastfeeding mothers.